Hyperactive delta isoform of PI3 kinase enables long-distance regeneration of adult rat corticospinal tract - Karova, Kristyna; Polcanova, Zuzana; Knight, Lydia; Suchankova, Stepanka; Nieuwenhuis, Bart; Holota, Radovan; Herynek, Vit; Machova Urdzikova, Lucia; Turecek, Rostislav; Kwok, Jessica C; van den Herik, Joelle; Verhaagen, Joost; et al. (Molecular therapy, 2025)
Neurons in the CNS lose regenerative potential with maturity, leading to minimal corticospinal tract (CST) axon regrowth after spinal cord injury (SCI). In young rodents, knockdown of PTEN, which antagonizes PI3K signaling by hydrolyzing PIP3, promotes axon regeneration following SCI. However, this effect diminishes in adults, potentially due to lower PI3K activation leading to reduced PIP3. This study explores whether increased PIP3 generation can promote long-distance regeneration in adults. We used a hyperactive PI3K, PI3Kδ (PIK3CD), to boost PIP3 levels in mature cortical neurons and assessed CST regeneration after SCI. Adult rats received AAV1-PIK3CD and AAV1-eGFP, or AAV1-eGFP alone, in the sensorimotor cortex concurrent with a C4 dorsal SCI. Transduced neurons showed increased pS6 levels, indicating elevated PI3K/Akt/mTOR signaling. CST regeneration, confirmed with retrograde tracing, was evaluated up to 16 weeks post injury. At 12 weeks, ∼100 axons were present at lesion sites, doubling to 200 by 16 weeks, with regeneration indices of 0.1 and 0.2, respectively. Behavioral tests showed significant improvements in paw reaching, grip strength, and ladder-rung walking in PIK3CD-treated rats, corroborated by electrophysiological recordings of cord dorsum potentials and distal flexor muscle electromyography. Thus, PI3Kδ upregulation in adult cortical neurons enhances axonal regeneration and functional recovery post SCI.
Keywords: Animals; pyramidové dráhy; Female; axony; Phosphatidylinositol 3-Kinases; ženské pohlaví; Recovery of Function; poranění míchy; fosfatidylinositol-3-kinasy; neurony; signální transdukce; Signal Transduction; obnova funkce; regenerace nervu; Nerve Regeneration; Neurons; genetické vektory; Spinal Cord Injuries; modely nemocí na zvířatech; Class I Phosphatidylinositol 3-Kinases; Dependovirus; Pyramidal Tracts; Disease Models, Animal; fosfatidylinositol-3-kinasy třídy I; krysa rodu Rattus; zvířata; Genetic Vectors; Rats; Axons